2020
DOI: 10.1049/mnl.2019.0767
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitrogen flow ratio on the optical property of AlN deposited by DC magnetron sputtering on Si (100) substrate

Abstract: Aluminum nitride (AlN) films were deposited on Si (100) substrate at room temperature in different N 2 flow ratios (N 2 /(N 2 + Ar)) by direct current (DC) magnetron sputtering. AlN films were prepared with the N 2 flow ratios from 20 to 50%. The intensity of X-ray diffraction peak on (002) plane enhanced with the increase of N 2 flow ratio. When the flow ratio of N 2 was 50%, the AlN film tended to be the most preferred orientation of (002) plane with the value of full width half maximum being 0.34°. Optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…It has been reported that AlN crystal quality can deteriorate when deposited under the low F N2 . [ 41 ] However, as seen from the nitrogen concentration shown in Table S1, Supporting Information, the nitrogen concentration showed a negligible difference between the samples. Therefore, the improvement of crystallinity was not due to the difference in the chemical composition of each sample.…”
Section: Resultsmentioning
confidence: 98%
“…It has been reported that AlN crystal quality can deteriorate when deposited under the low F N2 . [ 41 ] However, as seen from the nitrogen concentration shown in Table S1, Supporting Information, the nitrogen concentration showed a negligible difference between the samples. Therefore, the improvement of crystallinity was not due to the difference in the chemical composition of each sample.…”
Section: Resultsmentioning
confidence: 98%
“…Among these methods, magnetron sputtering, MBE, MOCVD, and PLD stand out as prominent techniques [8,9]. MBE and MOCVD technologies are renowned for their ability to produce lms of exceptional quality, Their cost and deposition rates limitations impede their widespread industrial adoption [10]. On the other hand, magnetron sputtering offers several advantages, including uniform lm deposition, ease of operation, and precise control, positioning it as a well-established and preferred method for large-scale production of high-quality AlN thin lms [11].…”
Section: Introductionmentioning
confidence: 99%
“…There are two common targets used: Al target and AlN target [20][21][22][23]. Much work so far has indicated that the preparation of AlN films based on Al target hardly ensure an exact composition ratio of films [24][25][26]. Some researchers obtained AlN films using AlN target, which had solved the problem of element composition ratio [27].…”
Section: Introductionmentioning
confidence: 99%